2019
DOI: 10.1111/vde.12777
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐induced dorsal skin necrosis in sheep

Abstract: Background -Solar-induced thermal burns of dark skin over the dorsum have been reported in dogs, sheep and a pig.Objectives -This report describes an outbreak of solar-induced thermal burns over the dorsal skin of criollo and Texel sheep in Uruguay.Animals and methods -Cross-bred criollo and pure-bred Texel adult ewes from a flock of 80 animals presented with severe skin lesions. Eight animals were evaluated clinically and skin biopsy specimens were collected from three ewes for histopathology. Epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These are the main mechanisms related to skin necrosis affecting mostly the dorsal areas of affected sheep in this study. Previous reports of DTN in sheep are rare; it has only been described in Uruguay (García et al 2019) and Australia (Butler & Bergman 2006). This lack of knowledge, in our experience, has resulted in frequent misdiagnosis of DTN as other forms of dermatological disease, mostly primary or secondary photosensitization, that are ordinary diseases caused by several toxic plants in Brazil (Schwartz et al 2018, Mendonça & Riet-Correa 2023.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are the main mechanisms related to skin necrosis affecting mostly the dorsal areas of affected sheep in this study. Previous reports of DTN in sheep are rare; it has only been described in Uruguay (García et al 2019) and Australia (Butler & Bergman 2006). This lack of knowledge, in our experience, has resulted in frequent misdiagnosis of DTN as other forms of dermatological disease, mostly primary or secondary photosensitization, that are ordinary diseases caused by several toxic plants in Brazil (Schwartz et al 2018, Mendonça & Riet-Correa 2023.…”
Section: Discussionmentioning
confidence: 99%
“…The skin temperature was 39.6°C, demonstrating that the effects of absorbed radiation remained mainly on the surface of the wool (Haddade et al 2018), which may explain why the wooly sheep exhibited fewer lesions when compared to the short-haired sheep. In reports of thermal necrosis in sheep, recent clipping was the main predisposing factor to injury in sheep (Butler & Bergman 2006, García et al 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study revealed Pastinaca sativa as the cause of photosensitization via contact photodermatitis leading to severe necrotizing dermatitis in goats [ 39 ]. Recently, un-induced thermal burns leading to dorsal skin necrosis in Texel sheep were reported in Uruguay, particularly in obese sheep, sheep with dark skin or after sunlight exposure during hot months after shearing [ 40 ]. However, the evidence of solar-induced skin necrosis or photosensitization caused by plant contact or ingestion remains unproven for the goats of the Swiss pasture.…”
Section: Discussionmentioning
confidence: 99%